Unexpected ultrafast and highly efficient removal of uranium from aqueous solutions by a phosphonic acid and amine functionalized polymer adsorbent. (1st June 2021) - Zhang, Qinghua; Zhang, Shiao; Zhao, Jizhou; Wei, Peng; Wang, Changfu; Liu, Pan; Zhao, Xiaohong; Zeng, Kai; Wu, Faming; Liu, Zhirong
Abstract : P(DMAA–B2MP) was prepared by solvothermal polymerization and exhibits fast and efficient sorption of uranium(vi ) from aqueous solutions. Abstract : It is still important to develop novel technologies for the highly efficient extraction of uranium from aqueous solutions in good yields for resource sustainability and environmental safety. Herein, a novel phosphonic acid-amino bifunctionalized polymer adsorbent P(DMAA–B2MP) has been prepared facilely by solvothermal polymerization of diallylamine (DMAA) and bis(2-methacryloxyethyl) phosphate (B2MP). Due to the introduction of a high concentration of hydrophilic phosphonic acid and amino groups onto the as-synthesized polymer adsorbent, P(DMAA–B2MP) not only showed an ultrahigh adsorption capacity for uranium from aqueous solutions but also demonstrated an ultrafast adsorption rate. The maximum adsorption capacity ( q max ) of the P(DMAA–B2MP) based on the Langmuir model could reach as high as 657.8 mg g −1 at a pH of 4.5, which is much higher than that of all the polymer chelating resin adsorbents reported previously. The kinetic process indicated that U(vi ) adsorption onto P(DMAA–B2MP) achieved equilibrium within 15 min, which is also much shorter than that of most of the adsorbents. Besides, the polymer adsorbents also have good selectivity for uranium and excellent recyclability. Both XPS analysis and DFT calculation results confirmed that the excellent adsorption efficiency of P(DMAA–B2MP) for uranium was ascribed to the strong complexation with phosphine oxide and amino groups. This work may provide a convenient method to design adsorbents with ultrahigh adsorption capacity, ultrafast adsorption rate, high selectivity and excellent reusability, which is very significant for the practical recovery of uranium from aqueous solutions.